MPPT circuit with analog control suitable for solar cars. Issue 1 (10th June 2020) - Kano, Fumihisa; Kasai, Yuji; Kimura, Hideki; Funato, Hirohito
Abstract: This paper presents a maximum power point tracking (MPPT) circuit composed of analog circuits suitable for solar cars. The MPPT controller circuit, which consists of analog switches and two op‐amps achieved precise MPPT during solar power generation. This MPPT controller circuit was constructed using a small number of CMOS elements, and the circuit of the step‐up DC‐DC converter achieved a conversion efficiency higher than 98% as well as weight reduction. Eighteen of the proposed MPPT circuits were installed (in serial and in parallel) in a solar car called "2013 Tokai Challenger" at an international competition, and it was shown that it could generate sufficient power supply from solar power.